2013
DOI: 10.3897/zookeys.256.3871
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of zooplanktivorous haplochromine cichlids from Lake Victoria, Tanzania

Abstract: Two new species of zooplanktivorous haplochromine cichlids from Lake Victoria, Tanzania, are described and illustrated. These species closely resemble each other. Their affinities to other zooplanktivorous haplochromines from Lake Victoria are discussed. Haplochromis argens sp. n., which featured under nicknames (mainly Haplochromis “argens”) in more than 50 papers, was caught both in the Mwanza Gulf and the Emin Pasha Gulf, whereas Haplochromis goldschmidti sp. n. was only found in the Emin Pasha Gulf. Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
(106 reference statements)
1
5
0
Order By: Relevance
“…That our catches in the recovery period contained more hybrids than in the past among the closely related ''curved head'' detritivores (Seehausen et al 1997b;de Zeeuw et al 2010), confirms the impact of reduced water transparency on genetic differentiation, consistent with prediction 4. Mzighani et al (2010) found genetic evidence for a negative impact of turbidity on reproductive isolation of two zooplanktivorous haplochromines in the sub-littoral of the Mwanza Gulf.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…That our catches in the recovery period contained more hybrids than in the past among the closely related ''curved head'' detritivores (Seehausen et al 1997b;de Zeeuw et al 2010), confirms the impact of reduced water transparency on genetic differentiation, consistent with prediction 4. Mzighani et al (2010) found genetic evidence for a negative impact of turbidity on reproductive isolation of two zooplanktivorous haplochromines in the sub-littoral of the Mwanza Gulf.…”
Section: Discussionsupporting
confidence: 74%
“…In the recovery period, the mean number of individuals per haul had approached the level of that in the pre-collapse period again, but the total number of species caught in 75 catches in 2001 and 10 catches in 2005 was only about 22, arranged in six identifiable trophic groups (Table 4). Apart from individuals that could be identified to the species level, there were many others that seemed to be hybrids, especially among the closely related 'curved head' detritivores that mainly differ in male colouration (de Zeeuw et al 2010). It should also be noted that the resurgent fish were smaller (both in maximum size and size at first maturity) than those caught in the pre-collapse period.…”
Section: Environmental Parameters In Butimba Baymentioning
confidence: 99%
“…antleter, and E. paropius by its dorsal head profile, which is straight to incurved above the eye and moderately decurved in the other three detritivores (Goldschmidt et al, 1993). Also, the lower jaw in E. coprologus is longer, narrower, and more oblique than in these other three species (de Zeeuw et al, 2010).…”
Section: The Detritivorous Enterochromis Antleter Mietes and Witte 2010mentioning
confidence: 92%
“…The detritivore Enterochromis coprologus Niemantsverdriet & Witte 2010 (formerly known as E. "nigrofasciatus"; Witte et al, 1992) has a nuptial coloration that is almost completely blue-black while the dorsum, flank, and chest can have a silvery sheen (de Zeeuw et al, 2010). Next to detritus, diatoms and copepods made up a large part of its diet and it occurred in the sublittoral part of the Mwanza Gulf before the near extinctions (Goldschmidt et al, 1993;Witte et al, 1992).…”
Section: The Detritivorous Enterochromis Antleter Mietes and Witte 2010mentioning
confidence: 99%
“…Van Oijen (1991) re-examined both genera and concluded that all synapomorphic traits overlapped considerably and represented continuous morphoclines. Hoogerhoud (1984), Witte & Witte-Maas (1987), Snoeks (1994), de Zeeuw et al (2012), and Vranken et al (2019Vranken et al ( , 2020b found that not all species of Haplochromis could be classified unambiguously into one of Greenwood's (1979Greenwood's ( , 1980 genera. Furthermore, most of these genera seemed to be polyphyletic (Meier et al 2017;McGee et al 2020).…”
Section: Introductionmentioning
confidence: 99%